Early thirties : a novel - Duboff, Josh (Scout Press Books, 2025)
"Sometimes friendship can be its own love story. Victor and Zoey are getting old. Well, old-er. And it's beginning to be a real problem. Best friends since college they have been through thick and thin, poor and poorer, drunk and drunker throughout their twenties in New York. Victor has built a successful career writing celebrity profiles for one of the last glossy magazines left standing, and Zoey is working for a fashion startup that is desperately trying to figure out how to monetize influencers, but has definitely figured out how to create a toxic work culture. But their wild twenties where mistakes can be forgiven, and hangovers last just until the first bacon egg and cheese sandwich is now replaced with responsibility, deadlines, and regrets a greasy breakfast can't cure. Victor and Zoey both want something more, and when tragedy befalls Victor their once unbreakable bond is starting to show cracks. As Victor and Zoey begin to leave each other "on read" in their constant text thread, and push away what they feel might be the only true love of their lives, Josh Duboff spins an immersive, hilarious, and heartbreaking story about coming of age, finding yourself and maybe realizing growing up has just as much to do with the person you were as it does with the person you are desperately trying to become"--